Pelindungan Hak Asasi Manusia Minimal Terhadap Negara dalam Keadaan Darurat: (Minimum Human Rights Protection Of The State In Emergencies) - Irwan Triadi; Aldy Mirozul (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to analyze the protection of human rights at a minimum in the implementation of emergency constitution The research used is a critical analysis with a qualitative approach that involves the analysis of legal documents and related literature. This research reveals the formation of emergency constitutional regulations that still pay attention to human rights, which must be carried out at a minimum. The type of research used in researching the problems in this study is normative juridical. This research is a normative juridical research because the researcher will analyze the laws and regulations related to the implementation of the emergency constitution from the perspective of human rights. Library materials and secondary data can be called normative legal research or library research by collecting legal materials both primary, secondary and/or tertiary. The government has a strategic role in determining the emergency conditions of a country. Traffic conditions caused by military, civilian attacks and disease outbreaks that cause the state to be unable to implement constitutional law normally, if not immediately will threaten the safety of the community and the country. Therefore, it is necessary to have written regulations or laws that provide a framework of procedures, formalities and frameworks to manage emergencies. The results of the research are expected to provide a comprehensive overview of the central government's implementation guidelines in carrying out emergency state administration.